Comprehensive Analysis of Circulating microRNA Specific to the Liver, Heart, and Skeletal Muscle of Cynomolgus Monkeys. (May 2017) - Iguchi, Takuma; Niino, Noriyo; Tamai, Satoshi; Sakurai, Ken; Mori, Kazuhiko
Circulating microRNAs (miRNAs) could represent sensitive and specific biomarkers for tissue injury. However, their utility as biomarkers in nonclinical toxicological studies using nonhuman primates is limited by a lack of information on their organ specificity and circulating levels under resting condition of the animals. Herein, liver, heart, and skeletal muscle-specific expression patterns of miRNAs were determined in 27 tissues/organs from male and female monkeys (n =2/sex) by next-generation sequencing (NGS) analysis. This analysis revealed organ-specific miRNAs in the liver (miR-122), heart (miR-208a and miR-499a), and skeletal muscle (miR-206). Next, plasma was collected from conscious-naive male and female cynomolgus monkeys (n = 25/sex) to better understand the expressions of organ-specific circulating miRNAs. The absolute values of circulating miRNAs were quantified using a Taqman microRNA assay. MiR-1, miR-133a, and miR-208b showed preferential expression in the heart and skeletal muscles, whereas miR-192 was abundant in the liver, stomach, small intestine, and kidney. These miRNAs had identical sequences to their human counterparts. Six organ-specific miRNAs (miR-1, miR-122, miR-133a, miR-192, miR-206, and miR-499a) could be evaluated quantitatively by quantitative real-time reverse transcription polymerase chain reaction with or without preamplification. No significant sex differences were noted for these circulating miRNAs. For their circulation levels, miR-133a showed more than 900-fold interindividual variation, whereas miR-122 showed only a 20-fold variation. In conclusion, we profiled circulating organ-specific miRNAs for the liver, heart, and skeletal muscle of cynomolgus monkeys.